Chromatographic Separation and Identification of Many Chemical Compositions and Antibacterial Activity of Laurus nobilis - Sultan, Fatimah I.; Haddad, Mohammed Fadhil; AL-Tamer, Yassar Yahya; Mohammed, Mahmood Esmail (American Journal of Botany and Bioengineering, 2026)
Phytochemical and antimicrobial screening leaves of Laurus nobilis , It was included the separation and identification of some active constituents from the leaves of Laurus nobilis and their activities were tested against some types of gram positive, gram negative bacteria. The active constituents were separated through Soxhlet and Column Chromatography (CC) and The column was eluted using petroleum - ether-ethyl acetate at 10:1 V/V intervals to separate various terpene compounds and fatty acids of L1F1 extract from Laurel leaves, As 20 active compounds were diagnosed by a device GCMS analysis technique, an of them (Terpinen-4-ol, . Linalool, gamma.-Terpinene, Eucalyptol, Eucalyptol, alpha.-Terpinyl acetate)and separating of some free phenolic compounds. As 6 Phenolic compounds (Luteolin, Kaempferol, Kaempferol, Qurcetine, Rutin, Apigenin, P. Coumaric acid) were identified by High Performance Liquid Chromatography (HPLC). The active separated compounds (terpene ,fatty acids, phenolics), each according to it’s separation and purification, showed a different inhibitory effect against the micro-organisms (m.o) under study by using Disc Diffusion Method.